PERAN LAYANAN UNIT PELAKSANA TEKNIS DAERAH PERLINDUNGAN PEREMPUAN DAN ANAK DALAM MENANGANI KASUS KEKERASAN - PATRIANI, ERNY; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; SUPARMAN, SUPARMAN (GANEC SWARA, 2023)
The aim of this research is 1) To explain the forms of violence against women and children in West Sumbawa district. 2) To explain the role of the women's and child protection service unit in dealing with violence against women and children in West Sumbawa district. 3) To explain the factors inhibiting the role of the women's and child protection service unit in dealing with violence against women and children in West Sumbawa district. This study used descriptive qualitative method. Researchers collect data, observe, interview and document to obtain complete and detailed data. The research results show that 1) Forms of violence against women and children include: psychological/psychological violence, physical violence, sexual violence, trafficking, exploitation, neglect, other violence. 2) The role of UPTD PPA in handling cases of violence is that it is responsible for providing protection, rehabilitation and recovery for victims of violence, as well as providing assistance during the legal process and ensuring that victims of violence receive the best service and can feel safe and receive justice. 3) The inhibiting factors for UPTD in handling cases of violence are limited resources, lack of public awareness, lack of coordination between related agencies, legal problems, and patriarchal culture which is still strong in society.